Basic Psychological Needs as a Mediator Between Autonomy Support and Motivation - Gong, Jiaowei; Santoso, Agus (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: This study aimed to investigate the mediating role of basic psychological needs in the relationship between autonomy support and motivation among Indonesian university students.Methods and Materials: The research employed a descriptive correlational design involving 488 undergraduate students from various universities in Indonesia. Participants were selected based on the Krejcie and Morgan sample size table using stratified random sampling. Data were collected through three standardized self-report instruments: the Learning Climate Questionnaire (LCQ) for assessing autonomy support, the Basic Psychological Need Satisfaction and Frustration Scale (BPNSFS) for measuring need satisfaction, and the Academic Motivation Scale (AMS) for evaluating motivation. Descriptive statistics, Pearson correlation, and structural equation modeling (SEM) were used to analyze the data. SPSS-27 was used for preliminary analyses, and AMOS-21 was applied to test the mediating model.Findings: Descriptive statistics indicated high levels of autonomy support (M = 5.21), need satisfaction (M = 4.89), and motivation (M = 5.37) among participants. Pearson correlations showed significant positive relationships between all variables, with the strongest correlation observed between autonomy support and basic psychological needs (r = .64, p < .001). The SEM results confirmed good model fit (χ²/df = 1.93, CFI = 0.97, RMSEA = 0.043) and demonstrated that autonomy support had both direct (β = .26, p = .002) and indirect effects (β = .36, p < .001) on motivation through the mediating role of basic psychological needs. The total effect of autonomy support on motivation was substantial (β = .62, p < .001).Conclusion: These findings emphasize the importance of autonomy-supportive educational environments in fostering student motivation.